2005
DOI: 10.2117/psysoc.2005.66
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Control During Dual-Task Performance of Visual or Auditory Monitoring With Visual-Manual Tracking

Abstract: Thirty university students (15 females) performed tasks from the NASA Multiattribute Task Battery, which was used to manipulate the attentional processing resource demands of the tasks. Separate groups performed visual or auditory monitoring tasks singly and in combination with visual-manual tracking while heart period, respiratory sinus arrhythmia (RSA), and pre-ejection period (PEP) were recorded to determine the modes of cardiac control during task performance. The tracking single-task suppressed RSA and wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 28 publications
3
11
0
Order By: Relevance
“…However, we observed a different autonomic mode of control, known as uncoupled parasympathetic inhibition (no sympathetic changes with parasympathetic inhibition - Berntson, Cacioppo, & Quigley, 1993). This mode of control has been found in tasks involving perceptual-manual response without engagement of central processing resources (Backs et al, 2005). Our findings suggest that ruminating about one's transgression involved a certain degree of attention without a pronounced engagement of central resources.…”
Section: The Effects Of Being Begrudgedsupporting
confidence: 48%
See 1 more Smart Citation
“…However, we observed a different autonomic mode of control, known as uncoupled parasympathetic inhibition (no sympathetic changes with parasympathetic inhibition - Berntson, Cacioppo, & Quigley, 1993). This mode of control has been found in tasks involving perceptual-manual response without engagement of central processing resources (Backs et al, 2005). Our findings suggest that ruminating about one's transgression involved a certain degree of attention without a pronounced engagement of central resources.…”
Section: The Effects Of Being Begrudgedsupporting
confidence: 48%
“…Our hypothesis predicted that ruminating about one's transgression would elicit reciprocal sympathetic activation and parasympathetic inhibition, a pattern observed in tasks involving engagement of central processing resources (Backs, Rohdy, & Barnard, 2005), mild psychological stress, such as those using the Stroop Word Color Conflict Test with monetary inducement (Delaney & Brodie, 2000), and tasks eliciting acute psychological stress, such as those involving speech, mental arithmetic, or reaction time (Brindle et al, 2014). However, we observed a different autonomic mode of control, known as uncoupled parasympathetic inhibition (no sympathetic changes with parasympathetic inhibition - Berntson, Cacioppo, & Quigley, 1993).…”
Section: The Effects Of Being Begrudgedmentioning
confidence: 99%
“…Tasks that elicit executive attentional processes (for higher-order strategies during dual-task performance) elicit only decreases in PEP while tasks that require primarily perceptual/motor processing (e.g., manual tracking) elicit only decreases in HF-HRV. [13,14] Research has confirmed that these modes of autonomic control are elicited during simulated driving as well. For example, a number of studies have shown that simulated driving in which velocity is fixed (primarily a perceptual/motor processing task) elicits only a decrease in HRV.…”
Section: Enhancing Diagnosticity Through Use Of Cardiac Measuresmentioning
confidence: 79%
“…In turn, as people become more efficient, fewer executive processes may be necessary to perform the task later as opposed to earlier in practice. Although Backs (1998) showed that the use of executive processes for dual-task performance elicits significant sympathetic activity, Backs et al (2005) found that sympathetic activation wanes over time as the number of executive processes used for task performance presumably decreases.…”
Section: Discussionmentioning
confidence: 95%
“…Tasks that require primarily perceptual-motor processing (e.g., manual tracking) elicit uncoupled parasympathetic withdrawal (Backs, Rhody, & Barnard, 2005;Lenneman & Backs, 2000). In addition, Backs et al (2005) found that adding monitoring tasks that required perceptual-central and motor processing to a tracking task that required perceptualmotor processing (thus creating competition primarily for motor resources) increased parasympathetic withdrawal but had no effect on sympathetic activity. Finally, executive attentional processes (for higher-order strategies during dual-task performance) are thought to elicit uncoupled sympathetic activation (Backs, 1998).…”
Section: The Doctrine Of Autonomic Spacementioning
confidence: 99%